1996
DOI: 10.1021/es9505513
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Hydrogel-Based Reactive Matrix for Removal of Chloracetanilide Herbicides from Contaminated Water

Abstract: Biodegradable, high-affinity hydrogel-based beads may prove useful in the decontamination of waters containing pesticide residue. Ethanethiol-cellulose beads, with a thiol content of up to 160 μmol -SH mL-1 bead, were synthesized by a novel method using 1,1‘-carbonyldiimidazole followed by reaction with aminoethanethiol. The use of thiol-derivatized beads to remove metolachlor from aqueous solutions, via a nucleophilic substitution reaction involving the α-carbon of the chloroacetamido group of metolachlor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Optical enhancing properties of the HA-AuNPs prepared at different pH were tested with an environmental pollutant, BT, 40 in two different ways. First, a known aliquot of the pollutant was added to the HA-AuNP suspension.…”
Section: Resultsmentioning
confidence: 99%
“…Optical enhancing properties of the HA-AuNPs prepared at different pH were tested with an environmental pollutant, BT, 40 in two different ways. First, a known aliquot of the pollutant was added to the HA-AuNP suspension.…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of cellulose into highly reactive carbonate or carbamate intermediates ( 20 and 21 ) has been performed in order to activate beads for subsequent modification. , Also in these cases, the applied activation reagents are expensive and highly reactive, which implies that undesired side reactions may occur. Finally, thiol substituents have been attached to cellulose beads ( 48 ) to obtain materials that are reactive toward chlorinated compounds …”
Section: Functionalization Of Cellulose Beadsmentioning
confidence: 99%
“…In this respect it has been found that effluents of WWTP contain high levels of herbicides that escape treatment [12,13]. The degradation of triazine herbicides such as ametryn and insecticides such as methomyl has been well investigated and much work has been performed on the removal of pesticides from wastewater by special procedures such as oxidation or irradiation [14]. Few publications have dealt with elimination of pesticides in WWTP [15].…”
Section: Introductionmentioning
confidence: 99%